Antiviral activity of Sanicula europaea L. extracts on multiplication of human parainfluenza virus type 2 - Karagöz, A; Arda, N; Gören, N; Nagata, K; Kuru, A (JOHN WILEY & SONS LTD, 1999)
The antiviral activity of Sanicula europaea L. extracts against human parainfluenza virus type 2 (HPIV-2) was examined, The extract prepared from the leaves of the plant and a fraction separated from the crude extract with gel filtration chromatography were found to inhibit HPIV-2 replication without any toxic effect on Vero cells. The acidic fraction obtained from the crude extract of S. europaea leaves was found to be the most active fraction with plaque inhibition assay at non-cytotoxic concentrations. Unfortunately, antiviral activity was not detected in the molecules purified from the crude ethanol extract of Sanicula leaves. Copyright (C) 1999 John Wiley & Sons, Ltd,
Keywords: Sanicula europaea L.; Apiaceae (Umbelliferaea); antiviral activity; parainfluenza; Pharmacology & Pharmacy